Reduced expression of microRNA-100 confers unfavorable prognosis in patients with bladder cancer - Wang Sheng; Xue Sheng; Dai Yuanqing; Yang Jianfu; Chen Zhijun; Fang Xiwu; Zhou Wensheng; Wu Wei; Li Qingwen (BMC, 2012)
Abstract Objective MicroRNA-100 (miR-100) has been demonstrated to be downregulated in bladder cancer tissues, and enforced expression of this miRNA may inhibit cell growth and colony formation of human bladder cancer 5637 cells in vitro. However, the clinical significance of miR-100 in human bladder cancer has not yet been elucidated. Thus, the aim of this study was to investigate the diagnostic and prognostic values of miR-100 in this disease. Methods Expression levels of miR-100 in 126 pairs of bladder cancer and adjacent normal tissues were detected by TaqMan real-time quantitative RT-PCR assay. In order to determine its prognostic value, overall survival (OS) and progression-free survival (PFS) were evaluated using the Kaplan-Meier method, and multivariate analysis was performed using the Cox proportional hazard analysis. Results Expression levels of miR-100 in bladder cancer tissues were significantly lower than those in adjacent normal tissues (mean expression level: 2.6 ± 1.2 vs. 3.9 ± 1.5, P < 0.001). When categorized into low vs. high expression, low miR-100 expression was negatively associated with the stage (P = 0.01), the recurrence (P = 0.008), the progression (P = 0.01), and the death (P < 0.001) of patients with bladder cancer. Moreover, low miR-100 expression clearly predicted poorer PFS (P = 0.001) and OS (P < 0.001). In the multivariate analysis, low miR-100 expression was an independent prognostic factor for both PFS (P = 0.01) and OS (P = 0.008). Conclusion Our data offer the convincing evidence that miR-100 may play an important role in the progression of bladder cancer and that the reduced expression of this miRNA may be independently associated with shorter PFS and OS of patients, suggesting that miR-100 might be a potential marker for further risk stratification in the treatment of this cancer. Virtual slides The virtual slides' for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1105483419841671